WOMEN'S ATHLETICS AT THE OLIMPIC GAMES: THE BRASILIANS PARTICIPATION AT THE MARATHON COMPETITION. (Fiep Bulletin - online, 2013)
Investigates the historical and socio-cultural causes that raised difficulties to women's participation in athletics, especially Brazilian women in the Olympic marathon. In the Olympics, few feminine athletes from our country obtained an index to participate in the marathon. The lack of sporting culture in Athletics, the shortage of equipment and training sites, besides the small supply of professionals able to training people in this sport reinforces the perpetuation of that situation in Brazil. The article also points out that the study of the history of women's Olympic marathon is the study of women's struggle for equal conditions and, therefore, could integrate, as the other competitions of Athletics, the content of PE lessons. It is suggested that this could contribute to the Athletics, in its diverse forms, be better known, appreciated and practiced by men and women.
Keywords: Athletics; Olympic Marathon; Brazilian athletes.